AYURVEDA INTERVENTION IN FEMALE INFERTILITY DUE TO OVARIAN FACTOR - A CASE REPORT - Upasana Sharma; Sushila Sharma (International Journal of Ayurveda and Pharma Research, 2020)
Infertility is defined as inability of a couple to conceive after one year of regular unprotected sexual intercourse. Incidence of ovarian dysfunction in the form of Polycystic ovarian disease (PCOD) has become a leading cause of female infertility in today’s era. Polycystic Ovarian disease (PCOD) is a heterogeneous, multifactorial and polygenic endocrinal disorder. Acharya Sushrut explained about Bandhya Yonivya pada where Nashtartava is mentioned as the one and only symptom. In Ayurveda text word Aartava has been used extensively in different contexts; menstrual blood, ovum and ovarian hormones. Therefore Amenorrhea, anovulation, hormonal dysfunction can be considered as visible manifestations of Nashtartva. So, here an attempt has been made to explore Samshodhan (Virechan) as a possible line of treatment for Bandhya (Nashtartava). Material and method: Following is a case report of a female who was anxious to conceive after 4 years of active married life, along with H/O delayed menses. Her USG reports showed polycystic appearance of ovaries and anovulation was noticed in follicular study. During this case study evaluation of Shodhan therapy (Virechan) and Shaman therapy in infertility due to ovulatory dysfunction was done. Result: Before the treatment patient was a known case of infertility due to PCOD and after treatment she conceived and delivered a healthy female baby. Discussion: Line of treatment was to enhance potency of ovum and with the help of Virechankarma, regularize vitiated Vata Dosha, Shrotoshuddhi and Aartava janan. Conclusion: Ayurveda therapy can be used in patients of infertility due to PCOD for better outcome and no adverse drug effect was noticed.